Searching for the shadows of giants: the absorption signatures of protoclusters in the Lyman-alpha forest - Miller, Joel Sebastian Arthur (2022)
In this thesis, I use large scale state-of-the-art hydrodynamical cosmological simulations to investigate the Ly-α absorption properties of protocluster regions at redshift z∼2.4. Using the IllustrisTNG simulations, I investigate how the AGNproximity effect and hot, collisionally ionised gas arising from gravitational infall and black hole feedback changes the Ly-α absorption associated with the z≃2.4 progenitors of M≥10^14 M_☉ clusters. Within these protoclusters, I find that galaxy overdensities exhibit a weak anti-correlation with Ly-α transmission in tomographic maps of the intergalactic medium (IGM), but local HI ionisation enhancements due to hot T>10^6 K gas or nearby AGN can disrupt this relationship within individual protoclusters. On average, however, I find that strong reductions in the IGM neutral fraction are limited to within ≲5 h^−1 cMpc of the dark matter haloes. Local ionisation enhancements will therefore have a limited impact on the completeness of protocluster identification in tomographic surveys if smoothing Ly-α transmission maps over scales of ∼4 h^−1 cMpc, as is typically done in observations. However, if calibrating the relationship between the matter density and Ly-α transmission in tomographic maps using simple analytical models for the Ly-α forest opacity, the presence of hot gas around haloes may result in systematically lower estimates of the z=0 descendant mass of the most massive protoclusters.